Biosignatures of diverse eukaryotic life from a Snowball Earth analogue environment in Antarctica - Fatima Husain; Jasmin L. Millar; Anne D. Jungblut; Ian Hawes; Thomas W. Evans; Roger E. Summons (Nature Communications)
Abstract The ephemeral, supraglacial meltwater ponds of the McMurdo Ice Shelf’s undulating ice serve as analogues for refugia where eukaryotic organisms could have thrived during the Cryogenian period. The seafloor sediment and debris lined ponds support the growth of a diverse array of cyanobacterial mat communities and provide habitats for a variety of protists and meiofauna. Here, we show that these eukaryotic assemblages, assessed by steroid biomarker and 18S rRNA gene analyses, inform long-standing questions regarding the diversity of, and controls on, community composition in these environments. Sixteen photosynthetically active microbial mats from meltwater ponds, a 700-year-old relict microbial mat, and a microbial mat from the Bratina Lagoon were analysed for their sterol compositions. These sterols were subjected to simulated diagenesis via catalytic hydrogenation/hydrogenolysis affording their sterane hydrocarbon counterparts, facilitating comparisons with ancient settings. Pond salinity appeared to be a factor influencing the sterol distributions observed. Analyses of 18S rRNA gene sequences conducted on the modern mats independently confirm that the ponds host diverse eukaryotes, including many types of microalgae, protists, and an array of unclassifiable organisms. Our findings support the hypothesis that supraglacial meltwater ponds like those of the McMurdo ice are strong candidates for refugia that sheltered complex life during Snowball Earth episodes.